Reading the lattice QCD form factors of the Λb → Λc transition using a C-code. (1st October 2022) - Smith, Bradley; Rashed, Ahmed; Huo, Chen
Abstract: The Λ b → Λ c ℓ − ν ¯ ℓ process has been discussed in the literatures as a probe for new physics. This process receives contributions in new physics models from scalar, vector, and tensor hadronic currents. The form factors of these currents can be obtained from the quark model or the lattice QCD. In this work, we present a c-code to read the scalar, vector, and tensor lattice QCD form factors. The code is published on github (https://github.com/darkfiresmith96/Lattice_QCD ). A Mathematica code was used in reference Datta et al (2017 J. High Energy Phys. 8 131) to read the form factors. Our c-code is much faster than the Mathematica code where the ratio of the wall clock time for the c-code compared to the Mathematica code is 1:64.2 per data point. A web interface for user inputs is introduced.